2017
DOI: 10.21577/0100-4042.20170123
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Low-Cost Lab-Made Photoreactor for Preparation of Nanomaterials

Abstract: In this paper, a low-cost and versatile lab-made photoreactor was constructed for the preparation of nanomaterials such as gold nanoparticles and reduced graphene oxide. The power of the lab-made photoreactor can be easily adjusted according to the number of lamps turned on. Moreover, the lab-made photoreactor allows the utilization of different sources of irradiation with distinct wavelengths. Performance tests for production of gold nanoparticles showed reproducibility and equal efficiency as compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Diante dessas limitações, nossa motivação é a construção de equipamentos de baixo custo e o compartilhamento das ideias com a comunidade científica. 28 O objetivo do presente trabalho foi desenvolver um carretel de baixo custo, a partir do uso de motor de passo e com uso de microcontrolador, para enrolar os filamentos para impressoras 3D a partir de um extrusora portátil. O carretel permite a utilização de uma ampla gama de velocidades de rotação, possibilitando ao usuário determinar qual a velocidade mais adequada para enrolar o filamento polimérico e obter o diâmetro desejado.…”
Section: Artigounclassified
“…Diante dessas limitações, nossa motivação é a construção de equipamentos de baixo custo e o compartilhamento das ideias com a comunidade científica. 28 O objetivo do presente trabalho foi desenvolver um carretel de baixo custo, a partir do uso de motor de passo e com uso de microcontrolador, para enrolar os filamentos para impressoras 3D a partir de um extrusora portátil. O carretel permite a utilização de uma ampla gama de velocidades de rotação, possibilitando ao usuário determinar qual a velocidade mais adequada para enrolar o filamento polimérico e obter o diâmetro desejado.…”
Section: Artigounclassified
“…Ranging from lamps for thin layer chromatography over commercial LEDs to decommissioned units from standard or reverse phase liquid chromatography instruments, a number of these systems have been reported in the literature. [5][6][7][8][9] In addition to that, 3D printing technology has allowed precise engineering and production of miniaturized systems. [10,11] In this publication, we report on the design and the assembly of a low budget UV-Vis photoreactor.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the availability of defined light sources in chemical laboratories, self‐made systems have emerged as an alternative for access to photochemical transformations. Ranging from lamps for thin layer chromatography over commercial LEDs to decommissioned units from standard or reverse phase liquid chromatography instruments, a number of these systems have been reported in the literature [5–9] . In addition to that, 3D printing technology has allowed precise engineering and production of miniaturized systems [10,11] …”
Section: Introductionmentioning
confidence: 99%
“…Industrial wastewater from the textile, paper, pharmaceutical and cosmetics industries contains a wide range of the organic dyes, which are harmful not only to human health but also to all the eco systems (1). The textile and industrial dyes have been reported to be the largest group of toxic organic compounds (2).…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, a new variable, "effective photon concentration (I eff )," is defined for a better understanding of charge carrier generation and dye photodegradation. Two critical tasks are assigned to I eff variable: (1) this variable can be considered as a criterion for determining the optimum conditions of dye degradation. In other words, a deep understanding of the effective photon concentration in different operating conditions is beneficial to find the optimum parameters of CV degradation.…”
Section: Introductionmentioning
confidence: 99%